Work-family conflict’s mediating effect on the relationship between job insecurity and job satisfaction in the hospitality industry: Evidence from the Algarve, Portugal - Duarte, A. P. (2024)
This study examined work-family and family-work conflicts’ mediating effect on the relationship between hotel workers’ job insecurity and job satisfaction in the Algarve, Portugal. The final sample comprised 166 employees who voluntarily completed a survey. SPSS and PROCESS macro software was used to analyze the data. Multiple regression analysis revealed that job insecurity is significantly related to job satisfaction both directly and indirectly via work-family conflict. Family-work conflict does not significantly mediate the abovementioned relationship. Hotel managers should continually monitor and enhance employees’ job satisfaction including providing more job security and implementing practices that foster a work-family balance.